As funções da controladoria em estruturas organizacionais diferenciadas - Miranda, Rodrigo Oliveira (2014)
As a response to an increasingly competitive market, companies are going through a process of deep change such as the implantation of new technologies, higher standards of quality, lower costs, and product innovation. The continuity of organizations depends on these processes in which the main objective is to maximize the benefits of emerging opportunities. This is the environment where companies search restlessly for more methods which will result in top economic performance. The present study aims at analyzing controllership functions in companies which stand out for the formalization or not of a controllership administration unit in their organizational structures, while taking into consideration the Contingency Theory, which states that there is no fit-for-all solution for organizational problems because structural optimization will always depend on contingent factors such as organizational strategy, environmental uncertainty, size and so on. This research is of qualitative and descriptive nature. It employs literature searches and field techniques such as the application of questionnaires and interviews as instruments for gathering primary data which had been sent to four company managers. Two of these companies were provided with controllership administrative units in their structures and two were not provided with such formally structured units. Therefore, it is a multiple-case study. In addition to field research, information collected from company documents was also used. Content analysis was employed in the assessment of data, which include a set of techniques of communications analysis in order to obtain, by means of systematic procedures and descriptive objectives of message contents, indicators which will allow for the inference of knowledge related to production/reception conditions of these messages concerning controllership functions and other company aspects such as the profile of the professionals responsible for controllership functions. It was observed that there are indeed controllership functions in companies which are provided with this structured area as well as in companies which are not provided with formally structured controllership functions, which confirms the research presupposition. By taking into consideration the contingency theory, it was observed that company size represents a level of organizational complexity which requires the realization of controllership functions in a more systematic way so that organization goals may be reached. It has been perceived that the term artifact is already well known and disseminated in organizations since the companies use several of the artifacts mentioned in the literature, though the Budget and Tax Planning are the only ones used by all companies. It has been confirmed that in the four investigated companies, whether they are provided with a controllership unit or not, the managers responsible for the controllership functions always works in these tasks: preparing the budget and development of conditions for the realization of an economic management. It has been concluded that companies intend to adapt to changes which constantly occur in external environments, in which the greatest challenge faced by the controllership area or the area responsible for such functions consists of generating information which will provide an answer to the necessities of managers in their decision-making process, especially in alignment with the needs for information required by managers when they make strategic decisions.